Konceptualizacija človekovih pravic v 21. stoletju - Tkalec, Staša (Teorija in praksa, 2014)
The article highlights the importance of human rights theory in the globalised world, contrary to the predominant legal discourse and emphasis on implementation of the existing international human rights law. The article is based on the supposition that the quest for a single, uniform and everlasting human rights theory, especially the foundationalist approach to human rights, cannot assure their universality in the globalised world. By considering three types of social transformation - related to globalisation processes and relevant to the protection of human rights - the article argues for the plurality and co-existence of different theoretical approaches to human rights. The latter would make the ontology of human rights theory correspond better to the contemporary social reality and would make better use of the potential it carries.
Keywords: človekove pravice; družbena transformacija; foundationalism; fundacionalizem; globalisation; globalizacija; globalization; human rights; social transformation